The veterinary profession in Greece. Review of the present and prospects for the future. IV. Anticipated developments for veterinary science.B. Envisioned expansion of Veterinary role in allied sciences - ΧΑΤΖΗΟΛΟΣ ΒΑΣΙΛΕΙΟΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
With current scientific and technologic advances of DNA recombinants, creation of new forms of life which heretofore had even escaped imagination could, as is generally expected, well become a realization. Assuming that these manipulations will be aimed at improving mankind, it is our hope that specialized veterinarians will render outstanding services in this field. As an incentive discussed here some of the latest achievements in gene engineering primarily in animals, and secondarily in plants because of their importance in the maintenance of healthy and highly productive animals. In addition, mention is made of the most recent developments in the fields of cancer and encephalines through animal research with the prediction that veterinary science will inevitably expand into these and other related fields, and that veterinarians will certainly participate in scientific challenges toward the improvement of the quality of life for animals and for man.